ANALISIS PENGARUH KOMPENSASI FINANSIAL DAN KOMPENSASI NON FINANASIAL TERHADAP KINERJA PEGAWAI PADA BADAN PUSAT STATISTIK (BPS) PROVINSI NUSA TENGGARA BARAT - isa isa (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2015)
This study aims to investigate the effect of financial and non-financial compensation, eitherpartially or simultaneously, on the employee work performance of Central Bureau of Statistics ofWest Nusa Tenggara. The study also aims to determine the most dominant variablesinvestigatedthat affect the employee work performance. The study uses an associative-causal researchapproach aiming to reveal the relationship between two or more variables. Population of the studyconsisted of 68 people and they were taken entirely as a respondent. To collect data, aquestionnaire instrument was used. Proir to the study, the instrument was tested todetermine itsvalidity and reliability. Further, the study employed multiple linear regression with statistical test ofdetermination (R2), t-test (partial test), F-test (simultaneous test),and individual coefficient ofdetermination (r2 test). Result of the study show that: (1) Financial Compensation had no significanteffect on the employee performance but non financial compensation did significantly influence theemployee performance. (2) There was a significant effect of the simultaneous FinancialCompensation and Nonfinancial Compensation on the Employee Performance. (3) The nonfinancialCompensation had indeed a dominant influence on the employee performance. For futureresearch,it is suggested if the study analyzed the effect of compensation on employee performance,especially in government agencies that have earned remunisasi (Performance Benefit),futureresearchers not include financial compensation variables and add other variables that can affect theemployee work performance such as employee behaviors, leadership style, working conditions,working environment, the complexity of task, and other similar others.From the theory ofindependent variables studied should be even more so that it can be seen that the dominantvariable and the most dominant influence employee performance.Keywords: Employees performances, Financial Compensation, Non Financial Compensation..